A inconstitucional averbação pré-executória veiculada pela Lei n. 13.606/2018 - Barbosa, Maria Carolina Guarda Ramalho (2020)
The purpose of this dissertation is to demonstrate that the pre-enforceable registration, instituted by Law n. 13.606/2018 and regulated by administrative rule n. 33/2018, frontly violates the Federal Constitution reflecting directly in the taxpayers assets. As this is a study with scientific intentions, we initially discussed issues related to the General Theory of Law, so that we will clarify the legal norm, identify the reference system adopted, as well as establish the premises to be adopted throughout the development of this study, passing through the notion of legal system, the characterization of antinomies, along with the ways of solving such conflicts. Then, we will approach the existing procedural model and the principles that we believe are essential to the application of the mentioned model. Then, we will analyze the existing mechanism in our legal system capable of investigating duly constituted tax credit, namely: tax enforcement. We will comment on its historical aspects, requirements for its distribution and its guiding principles. Next, we will detail the changes promoted by Law n. 13.606/2018, regulated by administrative rule n. 33/2018, as well as we will verify the concept and the origin of the pre-enforceable registration so that we can then analyze the violations instituted by Law n. 13.606/2018 to the provisions of article 146 of the Federal Constitution. In addition, we will make notes on article 185-A of the National Tax Code and Precedent 375 of the Superior Court of Justice. Once these specificities have been analyzed, we will discuss the Direct Actions of Unconstitutionality, which are in agreement with our understanding and, therefore, with the conclusion of this work